“There’s a Lot that Goes on in These Communities”: The Sexual Victimization of Minors in Rural and Remote Communities - Huey, Laura (Victims & offenders, 2024)
This study examines the sexual victimization of children and youth in rural and remote communities to uncover the types of victimization youth experience, and the criminal justice system challenges victims experience in these areas. We draw upon a thematic analysis of data (n = 83) from in-depth, semi-structured qualitative interviews and focus groups with police officers, youth, and adult community representatives from Canadian rural and remote regions. Results reveal that children and youth in rural and remote communities have experiences with particular forms of victimization, such as sending and sharing sexualized images without consent and sexual contact. We also identified significant challenges with reporting, police responses, and the court system, acutely informing victimization rates. Public policy implications are then offered, along with areas for further research.